2021
DOI: 10.1002/lary.29960
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Applied to White Light and Narrow Band Imaging Videolaryngoscopy: Toward Real‐Time Laryngeal Cancer Detection

Abstract: Objectives: To assess a new application of artificial intelligence for real-time detection of laryngeal squamous cell carcinoma (LSCC) in both white light (WL) and narrow-band imaging (NBI) videolaryngoscopies based on the You-Only-Look-Once (YOLO) deep learning convolutional neural network (CNN).Study Design: Experimental study with retrospective data. Methods: Recorded videos of LSCC were retrospectively collected from in-office transnasal videoendoscopies and intraoperative rigid endoscopies. LSCC videofram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 26 publications
0
55
1
1
Order By: Relevance
“…In the literature [16], the improved CBF (Counting Bloom Filter) module based on CBF and a Specter module replacing CSP module were proposed to realize the lightness of YOLOv5s model, and improve the detection speed and accuracy of picking Zanthoxylum fruit. In terms of medicine [17], the LSCC (Laryngeal Squamous Cell Carcinoma) using the integrated algorithm (YOLOv5s + Yolov5M-TTA) had the best results, and its performance indicators were comparable to those reported by other state-of-the-art detection models. In the literature [18], an assist system including embedded system jetson AGX Xavier and binocular depth camera zed 2 was proposed to help visually impaired people walk outdoors.…”
Section: Related Workmentioning
confidence: 80%
“…In the literature [16], the improved CBF (Counting Bloom Filter) module based on CBF and a Specter module replacing CSP module were proposed to realize the lightness of YOLOv5s model, and improve the detection speed and accuracy of picking Zanthoxylum fruit. In terms of medicine [17], the LSCC (Laryngeal Squamous Cell Carcinoma) using the integrated algorithm (YOLOv5s + Yolov5M-TTA) had the best results, and its performance indicators were comparable to those reported by other state-of-the-art detection models. In the literature [18], an assist system including embedded system jetson AGX Xavier and binocular depth camera zed 2 was proposed to help visually impaired people walk outdoors.…”
Section: Related Workmentioning
confidence: 80%
“…imagingbased navigation, neuromonitoring, different light filters and artificial intelligence tools) in a unified view. This may lead to a better identification of essential anatomic landmarks and superficial/deep tumour extension, thus refining surgical access and tumour resection through the growing field of videomics [51][52][53].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…With regard to real-time detection, Matava et al ( 19 ) and Azam et al ( 20 ) developed CNN algorithms that were applied in real time during videoendoscopy and which aimed at identifying, on the one hand, normal airway anatomy and, on the other hand, UADT lesions. Using this type of approach, DL may be a useful complementary tool for clinicians in endoscopic examinations, progressively implementing the concept of human–computer collaboration.…”
Section: Aims Of Videomicsmentioning
confidence: 99%
“…ResNet and Inception achieved a specificity of 0.98 and 0.97 and a sensitivity of 0.89 and 0.86, respectively. Finally, Azam et al ( 20 ) identified a CNN model for real-time laryngeal cancer detection in WL and NBI videoendoscopies. The dataset, consisting of 219 patients, was tested with an algorithm that achieved 0.66 precision (i.e., positive predictive value = true positives over true and false positives), 0.62 recall, and 0.63 mean average precision with an IoU > 0.5.…”
Section: Aims Of Videomicsmentioning
confidence: 99%